Bibliometric study on biofertilizers in Mexico during the period 2015-2020 - Coutino-Puchuli, Andrés Eduardo; Peña-Borrego, Maida Daylin; Infante-Jimenez, Zoe Tamar (REVISTA TERRA LATINOAMERICANA, 2023)
We characterized the trend of scientific research on biofertilizers in Mexico based on publications of national and foreign scientific journals during the 2015-2020 period. Our study consisted on the interpretation of research articles (in English and Spanish) published in the following scientific databases: Ebsco, Elsevier, Springer, Scielo, Wiley and Redalyc, for the analysis of bibliometric indicators. Productivity was determined by year, authors, journals, institutions, and collaborations between countries and Mexican states, on issues related to the use of microorganisms by agricultural crop, biofertilizer brands, and econometric variables and indicators. Within the evaluated period, a total of 115 research articles were published, with an annual average of 19 research articles. The most productive year was 2020, with 40 research articles. The authors with the greatest leadership in publications were Arturo Díaz Franco Santacruz and Cid Aguilar Carpio. The scientific journals that published the greatest number of these research articles were Terra Latinoamericana and Revista Mexicana de Ciencias Agrícolas. The main Mexican institutions performing the research were the National Institute of Forestry, Agriculture and Livestock Research (INIFAP) and the Postgraduate College. The United States of America is the country that collaborated the most with Mexican states (five states). Research in corn, varieties of chili, tomato, wheat and sorghum prevailed, being present in more than six research articles. Out of 33 brands of biofertilizers analyzed during the period, Micorriza INIFAP® was applied in more than 27% of the crops that used commercial biofertilizers. The most used microorganisms belonged to the genera Glomus, Pseudomonas, Bacillus and Azospirillum sp. Most of the research papers on biofertilizers are developed in the areas of agronomy, biology and environmental sciences, specifically in studies treating certain agricultural crop, while there are only few studies in the area of administration or marketing.